Determination of aerosol optical thickness through the derivation of an atmospheric correction for short-wavelength landsat tm and aster image data: an application to areas located in the vicinity of airports at UK and Cyprus - Hadjimitsis, Diofantos G.; Clayton, Chris R I (My University, 2009)
Aerosol optical thickness is considered to be the most important unknown parameter of every atmospheric correction approach for removing atmospheric effects from satellite remotely sensed images. This study presents a description of the basics of the proposed atmospheric correction procedure, which combines the darkest object subtraction principle and the radiative transfer equations. The method considers the true reflectance values of the selected dark targets acquired in situ and the atmospheric parameters such as the aerosol single scattering phase function, single scattering albedo and water vapour absorption, which are also found from ground measurements. The proposed procedure is applicable to short wavelengths such as Landsat TM band 1, 2 and ASTER band 1 in which water vapour absorption is negligible. The proposed image processing method has been tested successfully to determine the aerosol optical thickness on Landsat-5/TM images of the Lower Thames Valley area located to West London (UK) in the vicinity of Heathrow Airport and to Landsat TM/ETM+ and ASTER images of an area located in the vicinity of Paphos International Airport (Cyprus). The determined aerosol optical thicknesses for the Heathrow Airport area were 0.60, 013 and 0.75 for the Landsat TM images (0.45–0.52 μm) acquired on 17th of May 1985, 2nd of June 1985 and 4th of July 1985. The determined aerosol optical thicknesses for the ASTER (0.52–0.60 μm) images acquired on the 4th of February 2008, 26th of February 2008, 17th of December and 24th of December 2007 were 0.18, 0.39, 0.49 and 0.90, respectively. The accuracy assessment applied using the in situ spectroradiometric and sun-photometer data during the satellite overpass acquired on July–August 2008 for the Paphos area in Cyprus shows satisfactory results both for removing the atmospheric effects and for determining the aerosol optical thickness. Indeed, the high correlation between the determined aerosol optical thickness and those extracted from the visibility values increases the potential of the proposed method.
Keywords: Aerosol optical thickness; Landsat TM; ASTER; Atmospheric correction